Tribological properties of trichlorosilane-based one- and two-component self-assembled monolayers - Singh, R. Arvind; Kim, Jinseok; Yang, Sung Wook; Oh, Jae-Eung; Yoon, Eui-Sung (ELSEVIER SCIENCE SA, 2008)
Nano-scale adhesion and nano/micro-scale friction properties of one-component (pure) trichlorosilane self-assembled monolayers (SAMs) with different chain lengths and their two-component mixtures coated on silicon wafer (1 0 0) were experimentally studied. The tribological behaviour of these monolayer systems was compared with that of the uncoated silicon wafer. The nano-scale friction and adhesion forces were measured using atomic force microscopy (AFM) and the micro-scale friction tests were conducted using a custom-built micro-tribo tester. At both nano- and micro-scales, the pure SAMs and their mixtures outperformed the uncoated silicon wafer and were proved to be effective lubricants. At the nano-scale, both the friction and adhesion of pure SAMs decreased with the increase in chain length, and the mixed monolayers exhibited lower values of friction and adhesion than their pure counterparts. However, at the micro-scale, though the friction values of the pure SAMs decreased with the increase in the chain length, their mixtures exhibited values that were in between those of their individual components. The tribological behaviour of SAMs and their two-component systems observed in the present case has been explained by considering models available in literature. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: ATOMIC-FORCE MICROSCOPY; CHAIN-LENGTH DEPENDENCE; FRICTIONAL-PROPERTIES; CH3-TERMINATED FILMS; BOUNDARY LUBRICATION; SURFACE; GOLD; ALKANETHIOLS; SILICON; OCTADECYLTRICHLOROSILANE